Methodological Approaches to Risk Management of Advanced Therapy Medicinal Products - A. A. Taube; N. Yu. Velts (Разработка и регистрация лекарственных средств, 2023)
Introduction. Advanced therapy medicinal products (ATMPs) rely on recent advances in medical science, but alongside with potential benefits they may also bring safety concerns for patients. The inherent complexity of the ATMP production and use calls for special approaches to risk management throughout their lifecycle, from obtaining the raw materials to administration to the patient.Aim. The aim of the present study was to develop approaches to risk management for ATMPs, using the example of CAR T-cell therapy.Materials and methods. The study analysed the relevant regulatory frameworks currently in force in the European Union and the United States of America, namely the regulations and guidelines adopted by the Center for Biologics Evaluation and Research of the U.S. Food and Drug Administration and the Committee for Medicinal Products for Human Use of the European Medicines Agency.Results and discussion. The paper provides a classification of patient risks, which was developed based on the European risk-based approach. It formulates the principles of risk management for each of the risks, depending on the stage of the product life cycle. Each type of risk was considered separately. The following risk minimization strategies were determined: compliance with the good practices, ensuring the necessary qualifications or expertise of all parties involved in the product life cycle. The main element of risk control is the detailed description of the medicinal product use in the summary of product characteristics and patient information leaflet.Conclusion. The study identified the main stages at which ATMP risks may occur, and each type of risk was considered separately. The following requirements should be put in place in order to manage the ATMP risks: requirements for distributors on how to perform the product transportation and storage and to keep records for the marketing authorisation holder; requirements for healthcare facilities on how to perform the product storage, its preparation for use, advising and informing the patients on the treatment risks, symptoms of adverse events, preparatory and follow-up medical procedures, and on how to keep records for the marketing authorisation holder; requirements for the qualifications of healthcare professionals who are in charge of the product storage, its preparation for use, treatment procedures, advising and informing the patients on the treatment risks, symptoms of adverse events, and follow-up medical procedures. The data obtained will be used in the preparation of recommendations for ATMP developers.